Surface-Alloyed Nanoporous Zinc as Reversible and Stable Anodes for High-Performance Aqueous Zinc-Ion Battery - Meng, Huan; Ran, Qing; Dai, Tian-Yi; Shi, Hang; Zeng, Shu-Pei; Zhu, Yong-Fu; Wen, Zi; Zhang, Wei; Lang, Xing-You; Zheng, Wei-Tao; Jiang, Qing (Nano-micro letters, 2022)
Highlights Zn x Cu y alloy shell was in-situ formed on self-supported three-dimensional nanoporous Zn anode by anionic surfactant-assisted surface alloying of Zn and Cu. The self-supported nanoporous Zn x Cu y /Zn anodes exhibit high-rate capability, outstanding reversibility and stability during Zn stripping/plating because of zincophilic Zn x Cu y to guide uniform Zn deposition and facilitate Zn stripping. Aqueous Zn-ion batteries assembled with nanoporous Zn x Cu y /Zn anode and K z MnO 2 cathode achieve specific energy of as high as ~430 Wh kg ‒1 and retain ~86% after long-term cycles for >700 h. Metallic zinc (Zn) is one of the most attractive multivalent-metal anode materials in post-lithium batteries because of its high abundance, low cost and high theoretical capacity. However, it usually suffers from large voltage polarization, low Coulombic efficiency and high propensity for dendritic failure during Zn stripping/plating, hindering the practical application in aqueous rechargeable zinc-metal batteries (AR-ZMBs). Here we demonstrate that anionic surfactant-assisted in situ surface alloying of Cu and Zn remarkably improves Zn reversibility of 3D nanoporous Zn electrodes for potential use as high-performance AR-ZMB anode materials. As a result of the zincophilic Zn x Cu y alloy shell guiding uniform Zn deposition with a zero nucleation overpotential and facilitating Zn stripping via the Zn x Cu y /Zn galvanic couples, the self-supported nanoporous Zn x Cu y /Zn electrodes exhibit superior dendrite-free Zn stripping/plating behaviors in ambient aqueous electrolyte, with ultralow polarizations under current densities up to 50 mA cm ‒2 , exceptional stability for 1900 h and high Zn utilization. This enables AR-ZMB full cells constructed with nanoporous Zn x Cu y /Zn anode and K z MnO 2 cathode to achieve specific energy of as high as ~ 430 Wh kg ‒1 with ~ 99.8% Coulombic efficiency, and retain ~ 86% after long-term cycles for > 700 h.